2022
DOI: 10.3389/fvets.2022.909039
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Detection of Copy Number Variations and Evaluation of Candidate Copy Number Polymorphism Genes Associated With Complex Traits of Pigs

Abstract: Copy number variation (CNV) has been considered to be an important source of genetic variation for important phenotypic traits of livestock. In this study, we performed whole-genome CNV detection on Suhuai (SH) (n = 23), Chinese Min Zhu (MZ) (n = 11), and Large White (LW) (n = 12) pigs based on next-generation sequencing data. The copy number variation regions (CNVRs) were annotated and analyzed, and 10,885, 10,836, and 10,917 CNVRs were detected in LW, MZ, and SH pigs, respectively. Some CNVRs have been rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Zhang et al discovered that, compared to Chinese domestic pigs and Large White pigs, the identified Neural Glycoprotein 4 X-linked (NLGN4X) and Neural Glycoprotein 4 Y-linked (NLGN4Y) in Su-Huai pigs are associated with neurological diseases and neural signal transduction. This suggests that Su-Huai pigs are more docile and easier to domesticate than Large White pigs [ 21 ]. In enriched environments, swine have a higher level of proteins related to protein synthesis and neural activity, enabling them to better cope with stressful conditions like those found in slaughterhouses [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al discovered that, compared to Chinese domestic pigs and Large White pigs, the identified Neural Glycoprotein 4 X-linked (NLGN4X) and Neural Glycoprotein 4 Y-linked (NLGN4Y) in Su-Huai pigs are associated with neurological diseases and neural signal transduction. This suggests that Su-Huai pigs are more docile and easier to domesticate than Large White pigs [ 21 ]. In enriched environments, swine have a higher level of proteins related to protein synthesis and neural activity, enabling them to better cope with stressful conditions like those found in slaughterhouses [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these 758 CNVRs, we identified 19 CNVRs that overlapped with the reported CNVRs in this study with a total CNVR length of 699,128 bp. Zhang et al [ 22 ] performed genome-wide CNV detection on 46 pigs including Suhai, Minzhu, and Large White based on NGS data and 11,173 CNVRs were detected. Among these CNVRs, we identified 323 CNVRs that overlapped with the reported CNVRs in this study.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether the CNVRs identified in our study overlapped with those reported in previous studies, we compared our results in Duroc pigs to those CNVRs identified in several different swine studies[8,10,[19][20][21][22]. All CNVRs identified in other studies were converted to Sscrofa 11.1 genome assembly using the liftOver tool.…”
mentioning
confidence: 88%